2020
DOI: 10.1177/0960327120975448
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB1 receptor mediates METH-induced electrophysiological and morphological alterations in cerebellum Purkinje cells

Abstract: Our previous studies on cannabinoid type1 receptor (CB1R) activation on Methamphetamine (METH)-induced neurodegeneration and locomotion impairments in male rats suggest an interaction between CB1Rs and METH. However, the role of these receptors in METH-neurotoxicity has not been fully identified. Therefore, the purpose of the present study is to investigate the involvement of CB1Rs in these effects. We conducted an electrophysiological study to evaluate functional interactions between METH and CB1Rs using whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…It has been established that the PC is a unique kind of neuron that represents the only efferent neuron in the cerebellar cortex, essential for cerebellar function (Schonewille et al, 2021). It is well documented that the PC number is reduced in response to METH (Ramshini et al, 2021). Consistent with this study, we found a decline in PC number in mice cerebellum after METH intoxication, which could be alleviated by 10 and 20 mg/kg of MCC950.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It has been established that the PC is a unique kind of neuron that represents the only efferent neuron in the cerebellar cortex, essential for cerebellar function (Schonewille et al, 2021). It is well documented that the PC number is reduced in response to METH (Ramshini et al, 2021). Consistent with this study, we found a decline in PC number in mice cerebellum after METH intoxication, which could be alleviated by 10 and 20 mg/kg of MCC950.…”
Section: Discussionsupporting
confidence: 89%
“…It has been established that the nigrostriatal dopaminergic system is vulnerable to METH exposure since METH can be transferred into the cytoplasm by dopamine transporters (Huang et al, 2020). A recent study indicated that METH might lead to electrophysiological and morphological alternations of cerebellar PC (Ramshini et al, 2021). In the present study, we demonstrated that chronic METH could influence behavioral performance and cerebellar neurodegeneration involving a decrease in the number of PC, α-syn and p-Tau accumulation, axon degeneration, myelin sheath destruction and glial activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also reported mitochondrial dysfunction and increased neuronal death in the hippocampus after high doses of methamphetamine (41), however, lower doses have been found to be neuroprotective (42). Another study showed that methamphetamine treatment decreased the number of Purkinje cells in the cerebellum (43).…”
Section: Discussionmentioning
confidence: 99%
“…Etomidate-induced sedation was increased and prolonged by activation of the CB1 receptor in vivo in mice [19]. Importantly, numerous evidences show that cerebellar Purkinje cell expresses abundant CB1 receptors, suggesting that etomidate may modulate Purkinje cell activity via activation of CB1 receptors [20][21][22][23]. Our previous results show that etomidate facilitates CB1 receptors in the absence of GABA A receptors activity, resulting in a depression of the sensory stimulation-evoked synaptic transmission via protein kinase A (PKA) signaling pathway in mouse cerebellar granular layer [24].…”
Section: Introductionmentioning
confidence: 99%